Fracture Behavior of ASTM A633 steel plate specimens with edge crack at tensile test - Abi Shdid, Caesar (2017)
The tensile test is an important and widely used test to determine the mechanical properties of steel materials. In tensile test, a specimen is pulled and specimen deformation and applied load is recorded until its fracture to draw load-displacement curve. This work presents an experimental study of the mechanical behavior of the ASTM A633 grade high-strength low-alloy (HSLA) steel plate specimens with edge crack at the middle during the tensile test. Experimental analysis is used to analyze the loaddisplacement curve, and fracture surface around the crack. Also Finite Element Method (FEM) is used to see the J-integral curve for various crack lenghs. A633 HSLA steel plate specimens are tested in FIU Material Laboratory using a high capacity universal testing machine with various crack lengths. Phenom microscope is used to get the best images from the crack tip surface of the fractured samples. This paper evaluates the effect of crack length on the load-displacement curve and also fracture behavior of steel specimens is investigated after tensile tests. Results show that with crack length increasing, yield strength, the ultimate tensile strength, and fracture stress show a decreasing trend. Also, fracture will occur in the angle of principle shear stress.